Effects of Tariff on the Management of Blood Products in Fars Province Hospitals - Rohollah Baktashi MS; Fariba Rad PhD; Masoud Torabi Ardekani MD; Alireza Salah MS; Hossein Anani MS; Roohollah Mirzaee Khalilabadi PhD (Plasmatology, 2024)
Background In Iran, blood products were being delivered to healthcare centers without charge. For optimum usage and reducing wastage, the tariff was set on October 23, 2015. Thus, hospitals must pay for blood products to blood transfusion services and then the expenses are paid to healthcare centers by the insurance. Objectives This study aimed to explore the effects of the tariff policy on utilization pattern of blood products in healthcare centers of Fars province, Iran. Design This is a retrospective study which analyzes the recorded data. Methods Throughout this retrospective study, the number of units requested, delivered, returned, and return/delivery ratio of RBC, FFP, cryoprecipitate, and platelet were examined before and after the tariff in different cities of Fars province of Iran. Results After the tariff, return/delivery ratios of FFP, cryoprecipitate, and platelet increased in comparison with before tariff but were not statistically significant which means the return of unused units was increased after imposing tariff. Conclusion The results of this investigation showed that tariff may lead to more return of FFP, cryoprecipitate, and platelet units to the transfusion services of Fars province. More research must be performed to further approve it.